ENTREPRENEURIAL ORIENTATION, MARKET ORIENTATION AND DYNAMIC CAPABILITIES IN SMALL AND MEDIUM ENTERPRISES (Gestão & Regionalidade, 2019)
Entrepreneurial capacities are key to understand performance of businesses, especially in dynamic contexts, where sustaining competitive advantages is complicated. From this common statement on the capacities literature, the objective of this paper is to evaluate the role of dynamic capacities, entrepreneurship orientation and market orientation, in the performance of small and medium enterprises operating in Latin American market. The approach is quantitative, with non-experimental transectional design, and descriptive exploratory scope. The method consists of a random sampling of 330 companies that answered a survey questionnaire. Data are analyzed using descriptive statistics and correlation of variables. Results indicate that the environment is not dynamic, according to entrepreneurs, and variables —dynamic capabilities, entrepreneurial orientation, market orientation and performance— are statistically related.
Keywords: Dynamic capabilities; Entrepreneurial orientation; Market orientation; Performance